Energy Efficient Clustering Based Network Protocol Stack for 3D Airborne Monitoring System - Abhishek Joshi; Sarang Dhongdi; Rishabh Sethunathan; Pritish Nahar; K. R. Anupama (Journal of Computer Networks and Communications)
Wireless Sensor Network consists of large number of nodes densely deployed in ad hoc manner. Usually, most of the application areas of WSNs require two-dimensional (2D) topology. Various emerging application areas such as airborne networks and underwater wireless sensor networks are usually deployed using three-dimensional (3D) network topology. In this paper, a static 3D cluster-based network topology has been proposed for airborne networks. A network protocol stack consisting of various protocols such as TDMA MAC and dynamic routing along with services such as time synchronization, Cluster Head rotation, and power level management has been proposed for this airborne network. The proposed protocol stack has been implemented on the hardware platform consisting of number of TelosB nodes. This 3D airborne network architecture can be used to measure Air Quality Index (AQI) in an area. Various parameters of network such as energy consumption, Cluster Head rotation, time synchronization, and Packet Delivery Ratio (PDR) have been analyzed. Detailed description of the implementation of the protocol stack along with results of implementation has been provided in this paper.